Draf IIB with superior septectomy: finding the "middle ground". Issue 3 (12th December 2018) - Bhalla, Vidur; Sykes, Kevin J.; Villwock, Jennifer A.; Beahm, D. David; McClurg, Stanley W.; Chiu, Alexander G.
Abstract : Background: Previous studies have demonstrated a high failure rate of endoscopic sinus surgery (ESS) with Draf IIa in patients with diffuse polyposis, asthma, and aspirin‐exacerbated respiratory disease. A high percentage of these patients progress to endoscopic modified Lothrop procedure (EMLP). We describe a modification of the Draf IIb with a superior septectomy (IIb+SS), which may provide similar therapeutic benefit as demonstrated by the distribution of sinus irrigations in the sinus cavity with ESS with IIb+SS vs ESS with EMLP. Methods: ESS with IIb+SS was performed on 6 cadaver heads. Fluorescein‐dyed irrigations were performed on each head and penetration was recorded using video endoscopy. EMLP was subsequently performed on each head with repeat dye‐irrigation and video endoscopy. The videos were reviewed by 4 blinded fellowship‐trained rhinologists, and irrigant penetration of the maxillary, ethmoid, frontal, sphenoid sinuses, and olfactory cleft was graded 0 to 3 (3 implying complete staining). Results: The mean scores when comparing IIb+SS to EMLP were as follows: overall 1.99 vs 1.97 ( p = 0.816), maxillary sinus 2.67 vs 2.38 ( p = 0.128), ethmoid sinus 1.88 vs 1.98 ( p = 0.536), sphenoid sinus 2.58 vs 2.50 ( p = 0.467), frontal sinus 1.13 vs 1.38 ( p = 0.073), and olfactory cleft 1.71 vs 1.63 ( p = 0.529). There was no significant difference between subsites. Interrater reliability was good (Cronbach's alpha = 0.781). Conclusion: Performing ESS with IIb+SS provides similar irrigation delivery benefits to ESS with EMLP, without the need for altering natural sinus outflow and creating circumferential scarring. Further studies evaluating its use in patients that are high risk for revision surgery are needed.